2015
DOI: 10.1590/s1517-838246120131077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactants and temperature on germination and vegetative growth of Beauveria bassiana

Abstract: Three non-ionic surfactants: Tween20, Tween80 and Breakthru ® were screened for their effects on spore germination and mycelial growth rates and for their influence on three isolates of Beauveria bassiana spore germination at various temperatures. Tween20 and Tween80 were compatible with all the B. bassiana isolates in the germination studies, but inhibited germination at higher surfactant concentrations, irrespective of the conidial concentrations . Breakthru ® had an inhibitory effect on germination even at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 27 publications
4
31
0
4
Order By: Relevance
“…Accordingly, in P. chrysogenum metabolic changes are observed as stress result of adding detergents to liquid broths, with consequent production of different organic acids (Jakovljevi et al, 2014) Finally, Tween 40 and 80 did not enhance eritadenine yields, but biomass production did significantly. Similar growth stimulation by Tween 80 in submerged cultures have been observed in Beauveria (Mwamburi et al, 2015), and Armillaria sp. (Hadibarata and Kristanti, 2013).…”
Section: Eritadenine Yields With Surfactantssupporting
confidence: 79%
“…Accordingly, in P. chrysogenum metabolic changes are observed as stress result of adding detergents to liquid broths, with consequent production of different organic acids (Jakovljevi et al, 2014) Finally, Tween 40 and 80 did not enhance eritadenine yields, but biomass production did significantly. Similar growth stimulation by Tween 80 in submerged cultures have been observed in Beauveria (Mwamburi et al, 2015), and Armillaria sp. (Hadibarata and Kristanti, 2013).…”
Section: Eritadenine Yields With Surfactantssupporting
confidence: 79%
“…Selected surfactants have been shown by Chen et al, (2006) to restrain the degradation of polycyclic aromatic hydrocarbons by white-rot fungi. In other related studies, surfactants have been shown to inhibit spore germination and ergosterol production by fungi (Kozirog et al, 2018;Mwamburi et al, 2015;Tanuja et al, 2010). It can thus be generalized that surfactants puts a pressure on the hydrocarbon degrading ability of fungi, and this pressure can be relaxed in the presence of nutrients as observed in this study.…”
Section: Peekate Pl; Konne Jl; Abam Tkssupporting
confidence: 69%
“…Moreover, the level of moisture surrounding the insect is a key factor in forming germ tubes after the adhesion of conidia to the insect (Gaborty et al 2014;Devi and Bai 2015). The suitable moisture for conidia germination at the penetration and infection step should be above 95% (Mwanburi et al 2015). Fungi penetrate into the insect cuticle by producing various chitinase and proteases enzymes to degrade the coat compounds (Ortiz-urquiza and Keyhani, 2013).…”
Section: Discussionmentioning
confidence: 99%